Tailoring multifunctionality in coaxial twisted inorganic-organic core-shell yarns via composite design principles - Lei, Mengdie; Hu, Jiaman; Wu, Guilin; Wang, Zihao; Lv, Kun; Yang, Pengcheng; Lavorgna, Marino; Liu, Jize; Cai, Guangming (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Intelligent fabrics boasting capabilities in health protection, motion monitoring, and sensing play a pivotal role in advancing smart health management. However, achieving multifunctionality and mechanical robustness while ensuring sustainability remains a persistent challenge. Here, a biomimetic organic-inorganic strategy is proposed to develop a yarn with a coaxial multi-layer winding structure. It integrates high-strength basalt filament (BF) with degradable cotton slivers (CS), functionalized via a dynamic hydrogen-bonded epoxy soybean oil-based polymer. Leveraging the synergistic hydrogen-bonding interactions and coaxial winding structure, functional particles are stably incorporated into the yarn, endowing it with high tensile strength (182.84 MPa), remarkable impact resistance (85 % ± 1.2 % impact force attenuation), adjustable fluorescence for damage visualization, and self-healing capacity via reversible hydrogen bonds. Additionally, it exhibits biodegradability (12.7 % strength loss after 8 days) and component recyclability. When integrated into wearable systems, the yarn enables sensitive perception of environmental safety and real-time human health monitoring. This research effectively addresses the long-standing dilemma of balancing multifunctionality and environment sustainability in intelligent textiles, providing novel insights for developing next-generation advanced wearable multifunctional protective smart fabrics. [Display omitted] •Bioinspired organic-inorganic composite yarns with coaxial twisted structures•Biodegradable bio-based composite fiber system with dynamically reversible crosslinking networks•High mechanical properties (tensile strength: 182.84 MPa; attenuate >80 % of impact force)•Having cluster luminescence effect and can autonomous self-healing•Wireless-enabled intelligent protection fabric sensor for real-time perception monitoring